Leituras de paisagens urbanas: um estudo de Araguaína - TO - Pereira, Aires José (2013)
In order to understand the dominant concept of landscape today among and within the various sciences, as well as in arts, philosophy and common sense, it is interesting to study their history both temporally and spatially and also how societies in their intimacy have seen it with their own eyes. Thus, we will investigate the urban landscape reality Araguaína - TO, verifying their cultural traits inherited from their ancestors, through photographs and interviews with some of its residents. Authors such as Maximiano, Santos, Carlos, Venturi, Leite, Tuan, Landim, Razaboni, Corrêa, Marchezini, Bertrand, Damiani e Relph, among others, are of fundamental importance concerning the theoretical basis of the subject under discussion, especially in the first chapter. In the first chapter the methodology will deal basically with qualitative research, which will guide the thesis itself. In the second chapter we will aim at discussing the construction of Tocantins territory and its landscapes from the scenario created by mining evidenced in Goiás lands in the eighteenth century (its golden period) as well as through decadence. The alternatives found for extensive cattle breeding as a form of survival of its population and the marks printed on the construction of its landscapes and the territorial consolidation of Tocantins. For such purpose we highlight the works of the following authors: Lira, Assis, Aquino, Valverde, Martins, Duarte, Ferrari, Mesquita, Vinhal, Ajara, Parente, Cavalcante and Vesentini to understand the historical process of Tocantins territorial formation, throwing light on the federal public policies that acted directly in this spatial organization, such as the government plans, the construction of Goiania, Brasilia and major highways. The main objective of Chapter III is to understand the urban landscape of Araguaína as part of an entire historical, economical, ethical and cultural process of organization of this space, through interviews with the population. Throughout chapter IV the obstacles and the roughness of the urban development of Araguaína and its landscapes will be discussed. Problems such as high walls, pits in the sidewalks, appropriation of public space for private use, lack of urban forestry, urban fires, the issue of urban mobility and lack of accessibility to people with special needs will be addressed under the light of theory and also half of the interviewees\' statements. Finally, in the concluding remarks we will provide the city planners some urban proposals with greater sustainability.